The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7860/jcdr/2017/25706.9836
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Complete Blood Counts in Patients with Leptospirosis: Our Experience

Abstract: Complete blood count is a routine test done in the monitoring of patients with leptospirosis. Declining haemoglobin, marked thrombocytopenia and a normal to high total leukocyte count will help in early detection of severe disease and thus preventing mortality by timely management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…The vast variations in clinical presentations hinder the early accurate diagnosis, hence laboratory confirmation is critically needed to support the manifested signs and symptoms for initiating the treatment. In the present study, 92/165 patients with clinical manifestations suggesting leptospirosis were confirmed https://doi.org/10.1371/journal.pntd.0008197.g001 .07, which is in agreement with several other studies that ranged between 38.9-45 years [23][24][25][26][27]. About two thirds of the patients (n = 60; 65%) were males as observed in most studies [24-26, 28, 29].…”
Section: Discussionsupporting
confidence: 92%
“…The vast variations in clinical presentations hinder the early accurate diagnosis, hence laboratory confirmation is critically needed to support the manifested signs and symptoms for initiating the treatment. In the present study, 92/165 patients with clinical manifestations suggesting leptospirosis were confirmed https://doi.org/10.1371/journal.pntd.0008197.g001 .07, which is in agreement with several other studies that ranged between 38.9-45 years [23][24][25][26][27]. About two thirds of the patients (n = 60; 65%) were males as observed in most studies [24-26, 28, 29].…”
Section: Discussionsupporting
confidence: 92%
“…promoted the formation of mixed platelet–neutrophil aggregates. Thrombocytopenia is a common feature of leptospirosis, but its origin is still not clear (Adiga, Mittal, Venugopal, & Mittal, ; de Silva et al, ; Goeijenbier et al, ; Raffray et al, ; Tunjungputri et al, ). In this regard, the formation of circulating mixed aggregates could represent a possible mechanism that accounts for the clearance of platelets and the consequent thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of these infections is common during and after the rainy season. Clinical symptoms of these infections intersect each other and those seen in leptospirosis, typhoid fever and rickettsial infections 1,2,6‐9 . The latter three, though not as common as malaria and dengue fever, pose diagnostic difficulties in their early phases.…”
Section: Introductionmentioning
confidence: 96%
“…Clinical symptoms of these infections intersect each other and those seen in leptospirosis, typhoid fever and rickettsial infections. 1,2,[6][7][8][9] The latter three, though not as common as malaria and dengue fever, pose diagnostic difficulties in their early phases. The clinical presentation can vary from a mild febrile illness to lethal complications such as disseminated intravascular coagulation.…”
Section: Introductionmentioning
confidence: 99%